Bargaining and Strategic Discrimination - Jonas Björnerstedt; Andreas Westermark (Uppsala University, Department of Economics, 2006)
In bargaining between two sellers and one buyer on prices and quantities, strategic inefficiencies arise. By reallocating between the last agreement and the first, the buyer can increase it's share of the surplus. With symmetric sellers producing substitutes, the quantities in the first agreement will be higher than the efficient, and lower than the efficient in the last, implying that sellers are strategically discriminated. In equilibrium when the sellers produce substitutes, the buyer agrees first with the seller with lowest marginal cost. Efficiency is decreasing in the symmetry of the sellers and in the relative bargaining power of the sellers.
urn:nbn:se:uu:diva-83072
Keywords: C78; J22; J71; L10; 330; Bargaining; discrimination; intermediate goods; labor demand; Lieferanten-Kunden-Beziehung; Verhandlungstheorie; Preis; Neukeynesianische Makroökonomik; Diskriminierung